WHAT EVERY MANAGER SHOULD KNOW ABOUT FINANCIAL ANALYSIS - Donnahoe, Alan S., author 639780 (New York : Simon and Schuster)
Preface --1.Overhead: A Cautionary Tale --2.How to Read a Financial Statement --3.The Power of Compound Interest --4.Converting Future Dollars to Present Value --5.Return on Investment: Always the Key Question --6.Financial Ratios: The Vital Signs of a Company --7.Building a Budget: How and Why --8.What Pro Formas Really Mean --9.Cash Flow: The Real Test --10.Breakeven Analysis: X-Ray of Any Operation --11. How to Set Prices --12.The Competitive Impact of Operating Leverage --13.Cost of Capital: The Fundamental Ingredient --14.Corporate Use of Financial Leverage --15.What Dividend Payments Really Mean --16.How to Deal with Seasonal Variation --17.Stock Indexes Can Be Misleading --18.How to Read an Annual Report --19. Adjusting for Inflation --20.Hostile Takeovers and Mountains of Debt --21.Mergers and Acquisitions: Financial Strategy --22.Financial Frameworks for Compensation Systems --23.The Role of the Chief Fianacial Officer.